THE INFLUENCE OF AGRICULTURAL IMPORTS, FOREIGN IVESTATIONS, EXCHANGE VALUE ON INDONESIAN ECONOMIC GROWTH - M. Himawan Eko Rahmanto; Rr. Retno Sugiharti (Journal of Applied Economics in Developing Countries, 2021)
Various factors influence Indonesia's economic growth. The primary goal of this study is to examine the impact of agricultural imports, foreign direct investment (FDI), and the exchange rate on Indonesian economic growth from 1989 to 2019. Secondary data from 1989 to 2019 was used in this study, and it included variables such as economic growth, agricultural exports, agricultural imports, foreign direct investment (FDI), and exchange rates. The information came from the World Bank. An econometric model employing the ECM (Error Correction Model) method is utilized to prove the research hypothesis, and it is estimated using the E-Views version 10 application. Keywords: Economic Growth, Imports of agricultural commodities, Foreign Investment, Exchange Rate, Error Correction Model